Implementasi Kebijakan Izin Mendirikan Bangunan Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bekasi - Caesar, Ray; Priyanti, Evi; Ramdani, Rachmat (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The objectives of this research are to determine and analyze the policy implementation of BuildingPermit at Office of One Stop Services and Investment of Bekasi City. Type of this research isqualitative by taking community and officers/staff office of One Stop Services and Investment ofBekasi City as informants which were determined purposively. Data collection methods includeparticipant observation, in-depth interviews, documentation, and triangulation, while data analysistechniques include data reduction, display the data and draw conclusions and verification. The result shows that policy implementation of Building Permit in the Bekasi City is already running, but it is not maximized due to the content of the policy such as low knowledge and understanding as well as the public awareness in acquiring of Building Permit. Involved resources have limitedness, both in terms of quality and quantity, while the context implementation (implementation environment) is not maximized due to the low level of compliance with policy targets because of slow and complex service.